The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.17660/actahortic.2004.636.77
|View full text |Cite
|
Sign up to set email alerts
|

Insight Into Alternate Bearing of Pecan

Abstract: The fundamental cause of alternate bearing in pecan [Carya illinoinensis (Wangenh.) K. Koch] is unknown, but is closely linked to the size of the dormant season carbohydrate pool. Nut yields (over a period of up to 78 years) were evaluated, for 66 cultivars, in regards to alternate bearing intensity (I). Best-fit regression analysis indicates no association between I and fruit ripening date (FRD) or nut volume; although, there was moderate association with post-ripening foliation periods (PRFP) in that I tends… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
18
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 10 publications
2
18
0
Order By: Relevance
“…Hypotheses for alternate bearing have undergone modification as more data became available. The current theory supports a two-level control with inhibitors and promoters determining induction during the previous growing season and the dormant season carbohydrate pool influencing pistillate flower development (Smith et al, 1986;Sparks, 2000Sparks, , 2003aWood, 2003;Wood and McMeans, 1981;Wood et al, 2003Wood et al, , 2004.…”
supporting
confidence: 65%
See 1 more Smart Citation
“…Hypotheses for alternate bearing have undergone modification as more data became available. The current theory supports a two-level control with inhibitors and promoters determining induction during the previous growing season and the dormant season carbohydrate pool influencing pistillate flower development (Smith et al, 1986;Sparks, 2000Sparks, , 2003aWood, 2003;Wood and McMeans, 1981;Wood et al, 2003Wood et al, , 2004.…”
supporting
confidence: 65%
“…Alternate bearing is the most significant horticultural problem facing pecan producers. Several reviews have been published on the subject (Barnett and Mielke, 1981;Monselise and Goldschmidt, 1982;Smith, 2005;Sparks, 1974Sparks, , 1975Sparks, , 1979Sparks, , 1986Sparks, , 2000Sparks, , 2003aWood, 1991;Wood et al, 2004). Initial research (Smith and Waugh, 1938) and later work suggested that stored carbohydrate concentrations during the winter markedly affected subsequent flowering (Malstrom, 1974;Wood, 1989Wood, , 1991Worley, 1979aWorley, , 1979b.…”
mentioning
confidence: 99%
“…The natural trait of alternate bearing by pecan (Carya illinoinensis) trees is accentuated by environmental stresses interacting with hormonal and energy reserves related to flowering physiology (Worley, 1979a,b;Wood, 1995Wood, , 2011Wood et al, 2004). Some environmental factors reduce photoassimilation by trees sufficiently to impact dormant season energy reserves (Smith & Waugh, 1938;Sparks, 1975;Wood, 1989Wood, , 2014Smith et al, 2007) and, thus, availability of sucrose at the onset of the subsequent growing season (Wood, 2014); therefore orchard management strategies are required that maximize the photoassimilative capacity of the canopy.…”
Section: Introductionmentioning
confidence: 99%
“…(Wood, 1993), as well as in other fruit crops (Monselise and Goldschmidt, 1982). Studies suggest the amount of nonstructural carbohydrates stored during winter may be closely linked to the flowering potential of pecan (Lockwood and Sparks, 1978;Smith and Waugh, 1938;Wood, 1988Wood, , 1989Wood, , 1991Wood, , 1995Worley, 1979aWorley, , 1979b. Nitrogen depletion by large crops occurs in pistachio (Pistacia vera L.) (Brown et al, 1995;Rosecrance et al, 1998;Weinbaum et al, 1994a), citrus (Citrus reticulata Blanco) (Golomb and Goldschmidt, 1987) and prune (Prunus domestica L.) (Weinbaum et al, 1994b).…”
mentioning
confidence: 99%